Can Elevation Affect the Distribution of Nymphalidae Butterflies Adjacent to the Protected Regions in the Eastern Himalayan Landscape of West Bengal, India? - Panchali Sengupta (Biology and Life Sciences Forum, 2025)
Studies on the influence of latitudinal and elevation gradient on species diversity, richness, and evenness are significant. The present study attempts to document the elevational distribution of nymphalidae butterflies in the surrounding regions outside the jurisdiction of the protected areas of the Eastern Himalayas. Determination of diversity, evenness, richness, dominance, and Gini’s coefficient was undertaken across six elevational belts (≤1500 masl, 1501–2000 masl, 2001–2500 masl, 2501–3000 masl, 3001–3500 masl, ≥3501 masl). The highest values of diversity (H’ = 6.34) and species richness (R1 = 2.497; R2 = 12.01) were represented by a mid-elevation peak at 2501–3000 masl. However, evenness values (E = 1.424; EBG = 0.951; Eq = 0.987) were greatest at ≥3501 masl. Topographical uniqueness coupled with the formation of cloud cover at higher elevation may provide a habitat sustaining montane forest specialist species. Such differences in elevation could probably influence the diversity and distribution of nymphalidae, with immense ecological significance.